Capturing the Integration of Practice-based Learning With Beliefs, Values, and Attitudes Using Modified Concept Mapping - McNaughton, S; Barrow, M; Warwick, B; Frielick, S (Libertas Academica, 2016)
Practice-based learning integrates the cognitive, psychomotor, and affective domains and is influenced by students’ beliefs, values, and attitudes. Concept mapping has been shown to effectively demonstrate students’ changing concepts and knowledge structures. This article discusses how concept mapping was modified to capture students’ perceptions of the connections between the domains of thinking and knowing, emotions, behavior, attitudes, values, and beliefs and the specific experiences related to these, over a period of eight months of practice-based clinical learning. The findings demonstrate that while some limitations exist, modified concept mapping is a manageable way to gather rich data about students’ perceptions of their clinical practice experiences. These findings also highlight the strong integrating influence of beliefs and values on other areas of practice, suggesting that these need to be attended to as part of a student’s educational program.
Keywords: Attitudes; Beliefs; Concept mapping; Practice-based learning; Values